Effect of season on performance of arum (Colocasia esculenta var esculenta) cultivars - Singh, J P; Singh, M K; Singh, R D (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during the rainy season of 1989--91 to study the yield and growth characters of 25 genotypes of arum [Colocasia esculenta (L.) Schott var esculenta Purseglove ] under irrigated condition. There were significant variations for genotypes and genotype x environment interaction for plant height, tubers/plant, tuber weight/ plant and tuber yield. 'FC 14' gave the highest tuber yield (23.07 tonnes/ha) followed by 'NDC 3' (21.96 tonnes/ha) and 'FC 4' (18.85 tonnes/ha). 'NDC 2', 'NDC 3' and 'FC 14' showed stability for number and weight of tubers/plant and tuber yield.